ANALYSIS OF PERFORMANCE PROPERTIES OF HYBRID PASSENGER CARS IN HOT CLIMATE CONDITIONS OF UZBEKISTAN - Rakhmankulov F. Kh; Sadullaev B.; Avliyokulov Zh. S.; Abdumannoev Z. A. (Sciental Journals Publishing, 2025)
The article is devoted to the analysis of the operation of vehicles with hybrid power plants in the internal combustion engine (ICE) and electric traction modes. The main advantages of hybrid vehicles when driving with an internal combustion engine (ICE) and an electric motor are considered. The influence of road conditions on the range and the energy recovery process is analyzed. Based on the results of the analysis of the performance properties of vehicles with hybrid power plants and experimental data, recommendations are obtained for the technical operation of this type of vehicles in the hot climate of the Republic of Uzbekistan.
Keywords: Batteries, hybrid vehicle, electric drive, electric charge, high-voltage battery (HVB), electronic control unit (ECU), recuperation, range, traction and speed properties, fuel efficiency.